MONETARY INEQUALITY AND INFLATION IN RUSSIA: OFFICIAL STATISTICS AND ASSESSMENTS OF POPULATION - Aleksandr Igorevich Rossoshanskii (Science and Innovation Center Publishing House, 2021)
The longstanding nature of significant income differentiation of the population and the instability of consumer prices affect the uneven distribution of resources and life opportunities among different groups of the population, exposing some of them to an increased risk of economic vulnerability. These problems are even more made worse during periods of instability in socio-economic life caused by political, anthropogenic or natural (for example, pandemic 2020) reasons. In this regard, the tasks of analyzing the emerging dynamics of inequality and inflation and identifying, on this basis, risks to the well-being of the population, acquire scientific and practical significance.